Writing Tool Use and Writing Self-Efficacy among EFL Undergraduate Students: A Preliminary Correlational Study - Tsaltsa Rafi'ah Pramono; Moh. Yamin; Inayati Fitriyah Asrimawati (English Teaching and Linguistics Journal (ETLiJ), 2026)
Writing is among the most cognitively demanding skills in English language learning, and self-efficacy has consistently been identified as one of its principal affective determinants. The rapid proliferation of digital writing tools raises the question of how their use relates to learners’ confidence in composing academic texts. This study examined the relationship between writing tool use and writing self-efficacy among undergraduate students of an English Language Education study programme, and additionally described the participants’ descriptive writing performance. A correlational design was employed. Nine students who had completed an advanced writing course and reported prior experience with writing tools participated voluntarily through self-selection sampling. Data were collected through a ten-item questionnaire adapted from Khosravi et al. (2017), which demonstrated acceptable internal consistency (Cronbach’s α = .712), and a descriptive writing test scored with an analytic rubric covering identification, description, language features, vocabulary, and mechanics. Pearson product-moment correlation revealed a strong, positive, and statistically significant association between writing tool use and writing self-efficacy (r = .778, p = .013, n = 9). Writing performance was uneven: 55.56% of the participants were categorised as good to average and 44.44% as fair to poor, with mechanics emerging as the weakest indicator (88.89% fair to poor) despite the fact that two-thirds of the participants reported using an automated grammar checker. The findings suggest that writing tools may support learners’ confidence without automatically translating into textual accuracy. Given the small, self-selected sample, the results are exploratory and warrant replication.